13. EVALUATION OF THE RESULTS TREATMENT URETHRAL VARICEAL BLEEDING BY URETHRAL ENDOSCOPIC TECHNIQUE AT VIET DUC UNIVERSITY HOSPITAL DURING THE PERIOD 2019 - 2022 (Vietnam Journal of Community Medicine, 2024)
Purpose: To evaluate the results of treatment urethral vericeal bleeding following urethral endoscopic technique at Viet Duc University Hospital during the period 2019-2022. Materials and methods: A descriptive study of urethral variceal bleeding treated by endoscopic urethral surgery from January 2019 to December 2022 at the Center of Andrology and Sexual medicine at Viet Duc University Hospital. Results: The mean age was 50 ± 11,34. Urethral bleeding during erection accounts for 51.6%. Transrectal ultrasound showed 25/31 patients with images of increased vascularity The mean operative time was 44 ± 17,84 minutes, the mean hospital stay was 5 ± 1,52 days. No patients had complications during surgery. There are 1 cases of recurrent bleeding that have been treated medically and are now completely stable. Conclusion: Endoscopic urethral technique is a safe and effective method for treatment urethral bleeding.